2017
DOI: 10.1007/s10072-017-2975-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in mild cognitive impairment: a systematic review of objective measures

Abstract: Sleep disturbance frequently occurs in patients with mild cognitive impairment (MCI) and appears to be involved in the cellular and molecular mechanisms of cognitive decline. The aim of this systematic review is to clarify whether patients with MCI demonstrate alterations in certain sleep parameters: total sleep time (TST), sleep efficiency (SE), sleep latency (SL), rapid eye movement latency (REML), percent of rapid eye movement (REM%), arousal index (AI), wake after sleep onset (WASO), slow-wave sleep (SWS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 30 publications
5
37
3
Order By: Relevance
“…Peculiar macrostructural sleep alterations have already been reported in MCI, particularly involving whole sleep parameters, such as total sleep time, whereas REM and N3 sleep reduction appear less consistent (for review, see Hu et al., ). In our study, total sleep time was decreased in both subgroups of patients with aMCI as compared with HE, but inter‐individual variability did not allow reaching statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Peculiar macrostructural sleep alterations have already been reported in MCI, particularly involving whole sleep parameters, such as total sleep time, whereas REM and N3 sleep reduction appear less consistent (for review, see Hu et al., ). In our study, total sleep time was decreased in both subgroups of patients with aMCI as compared with HE, but inter‐individual variability did not allow reaching statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Although experiments demonstrating an impact of insufficient sleep on brain function have been primarily conducted in healthy young participants, studies of sleep in older people indicate that sleep also contributes to brain functioning in the later stages of the life span ( 10 , 17 ). Some studies have reported correlations between sleep and cognition in particular age groups [e.g., ( 18 )] and patient groups such as those with mild cognitive impairment ( 19 ). In these studies age has rarely been treated as a continuous variable and in very few studies has sleep been assessed by polysomnography (PSG) ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of studies comparing objective sleep measures of patients with MCI with those of the healthy elderly showed that the former had shorter total sleep time, sleep efficiency, cycling alternating pattern (a measure of sleep instability) and longer sleep latency. Patients with nonamnestic MCI, on the other hand, had a greater total sleep time compared with the healthy elderly 12 . Other parameters, such as the wake time after sleep onset, slow-wave sleep, REM latency and REM (%), and periodic limb movement syndrome did not differ between the groups 12 .…”
Section: Sleep Changes In Mild Cognitive Impairmentmentioning
confidence: 91%
“…Some of its advantages are the low cost for an objective method, the convenience of execution, the low rate of interference in sleep quality and the possibility of mapping the total motor activity of the participant for longer periods, thus being suitable for circadian cycle studies. Also it is appropriate for diagnosing periodic limb movement syndrome 12 .…”
Section: Sleep Assessment and Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation